2008
DOI: 10.1002/adsc.200700418
|View full text |Cite
|
Sign up to set email alerts
|

Simple Methodology for Heck Arylation at C‐8 of Adenine Nucleosides

Abstract: A simple method for the arylation of 8-vinyladenine nucleoside derivatives is reported. With a broad set of aryl iodides and bromides, the reaction is catalyzed by the simple combination palladium acetate/trisA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…26 The vial was flushed with nitrogen gas and sealed with a Teflon-lined cap. The reaction mixture was stirred at 100 °C for 15 h, then diluted with EtOAc (10 mL), and washed with water and brine.…”
Section: Methodsmentioning
confidence: 99%
“…26 The vial was flushed with nitrogen gas and sealed with a Teflon-lined cap. The reaction mixture was stirred at 100 °C for 15 h, then diluted with EtOAc (10 mL), and washed with water and brine.…”
Section: Methodsmentioning
confidence: 99%
“…The optimized conditions (Pd/CuI/ t BuOLi) were applicable for the selective alkenylation of caffeine, benzimidazole and other aromatic azole heterocycles [45,46]. These are significant developments since it was reported that 8-bromoadenosine was not a good substrate for Mizoroki-Heck reaction [47] making modification at 8 position via direct functionalization of C8-H bond a desirable transformation.…”
Section: Direct Activation Of C8-h Bond In Purine and Purine Nuclementioning
confidence: 99%
“…In the realm of biological chemistry, in 2008, Lagisetty et al [46] reported for the first time a simple method for the arylation at C-8 of adenine nucleosides. The motivation for this investigation was the observation that substitution at the C-8 position can influence the syn-anti conformational equilibrium around the glycosidic bond or produce structural factors that can influence enzymatic recognition.…”
Section: Arylations With the Heck-mizoroki Reactionmentioning
confidence: 99%